Bio-Psycho-Social Profile of People with Substance Use Disorders Treated in Locally Assigned Treatment Facilities in Kandahar, Afghanistan - Stanikzai MH; Wahidi MW (Dove Medical Press, 2023)
Muhammad Haroon Stanikzai, Mohammad Wahid Wahidi Department of Public Health, Faculty of Medicine, Kandahar University, Kandahar, AfghanistanCorrespondence: Muhammad Haroon Stanikzai, Department of Public Health, Faculty of Medicine, Kandahar University, District # 10, Kandahar, 3801, Afghanistan, Tel +93704775578, Email haroonstanikzai1@gmail.comBackground: Substance use and its associated bio-psycho-social problems are public health concerns with harmful individual and social consequences.Objective: This study assessed the bio-psycho-social profile of people with substance use disorders (SUD) treated at locally assigned treatment facilities in Kandahar, Afghanistan.Methods: We conducted this facility-based cross-sectional study among 621 substance users receiving care at three locally assigned treatment facilities in November-December 2022. We performed multiple linear regression to determine factors associated with psychological symptoms.Results: The mean age of the participants was 34.41 (± 10.10 SD) years. The majority of our subjects (81.2%) perceived their physical health as very good or fair. More than two-thirds (73.4%) rated their social support as high. Of all participants, 541 (87.1%) had symptoms of depression, 569 (91.6%) of anxiety, and 442 (71.2%) of stress. The prevalence of severe depression, anxiety, and stress was 34.8%, 65.8%, and 27.3%, respectively. The multiple linear regression showed that several attributes of people with substance use disorders [ie, having a low level of education (β=0.12, p=< 0.001), being unemployed (β=0.31, p=< 0.001), having a low level of social support (β=− 0.35, p=< 0.001), had a pre-existing medical condition (β=− 0.28, p=< 0.001), and having lived abroad in the past ten years (β=0.10, p=0.001)] were significantly associated with higher DASS-21 total scores.Conclusion: This study highlights the importance of providing bio-psycho-social support programs and implementing therapeutic interventions to help people with substance use disorders, particularly those who are most susceptible to higher levels of bio-psycho-social problems.Keywords: depression, anxiety, stress, social support, co-morbidity, rehabilitation centers